Distributed hue recognition based k connectivity path detection in WSN - Shihua CAO; Keyong HU; Lidong WANG; Qihui WANG (Dianxin kexue)
In order to improve the accuracy of k connectivity path detection algorithm in wireless sensor network (WSN),a k connectivity path detection algorithm based on distributed hue recognition for WSN was proposed.Firstly,the model structure of the WSN network was given by use of the graph model,and the theoretical definition of the model was given.Secondly,according to the proposed WSN model,the disjoint paths for each node to the sink node were calculated,and cat culated using the minimum value,so as to achieve accurate detection of the boundary between the value of k.Finally,the validity of the algorithm was verified by experiment simulation.